Comparative Analysis of Reinforcement Efficiency in Beams and Columns for the North Minahasa-North Sulawesi Civil Servants Flats Project - Hendrie Palar; Kabo, Don; Herman Tumengkol (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to (1) compare the reinforcement from the calculation of beams and columns with the reinforcement installed in the North Minahasa Civil servantsFlats Project, (2) to analyze whether the reinforcement installed in the North Minahasa Civil servantsFlats Project is economical or not. This research was conducted in the Department of Engineering at the Manado State Polytechnic. The method used in this research is quantitative with the method of observation. The material and structural data used are the same as those in the project. The results of this study were carried out with the help of the Etabsv20 program. Based on the results of the reinforcement calculations that have been carried out, the comparison of the area of reinforcement (AS) for columns and beams between the results of ETABS and the results of the area of reinforcement installed in the project is obtained which is then converted in percentage form. In the beam, the largest percentage ratio is in the upper support area by 60% and in the plane located in the lower plane by 60%. While in the comparison column the percentage of reinforcement column (AS) from the project with the largest ETABS result is 40%